On Public Library Service Brands - Wang Shiwei (Contemporary Social Sciences, 2020)
This paper makes a comprehensive analysis of the building of public library service brands in China since the initiation of the reform and opening up in 1978 and anticipate their future development in five aspects, i. e., critical interpretation of its established culture and analysis of its characteristics, logic of the time, vivid practice, virtuous approaches, as well as future development.